Survei Pengendalian Hama Terpadu Hama Lalat Buah Bactroceraspp. Pada Tanaman Jeruk di Tiga Kecamatan Kabupaten Karo - Armeilia Yulanda Atmyanti Marpaung, Yusw Atmyanti Marpaung; Yuswani Pangestiningsih; Mukhtar Iskandar Pinem (Jurnal Agroekoteknologi, 2014)
Research Survey of integrated pest management fruit flyBactroceraspp on cytrus in threesubdistrict’s of Karo’s regency.The aim of this research was to find out relation between integratedpest management with the number of fruit flies imago, damage percentage and production of orangein three Karo regency. This research had been conducted at farmer field Simpang Empat, BarusJahe dan Tiga Panah, Kabupaten Karo pada May - September 2013 using survey method bycorrelation quantitative analyze rank Spearman. The result showed that the number of orange fruitflies had a significant corelation with damage percentage of fruit flies (rxy= 0,733), and integrated pestmanagement was not have the significant corelation with damage percentage (rx1y= 0,256) but had asignificant corelation with production of cytrus in Karo (rx1y1= 0,464). The highest number ofBactrocera spp imago were showed in Tiga Panah with 71,07 imago number and the lowest wereshowed in Barus Jahe with 23,76 imago number. The highest damage percentage were inTiga Panah 14,27% and the lowest damage percentage were in Barus Jahe 5,89%. The best orangeproduction were in Barus Jahe with 14,05 ton/ha/year, and the lowest production were inTiga Panah with 10,05ton/ha/year.Keywords: Cytrus, Bactrocera spp dan IPM.